Pre- and post-operative differences between genders in idiopathic macular holes - Wang, Jing (BMC Ophthalmol, 2020)
BACKGROUND: To compare idiopathic macular holes (IMHs) between male and female before and after surgery. METHODS: Patients with IMHs of stage 3 and stage 4 who underwent 23-gauge vitrectomy were retrospectively enrolled. Pre-operative clinical features like age of onset, and best-corrected visual acuity (BCVA) were reviewed. Optical coherence tomography parameters including minimum linear diameter (MLD), central macular thickness and some other indexes were measured and calculated. Main surgical outcomes included the primary closure rate, the highest BCVA during follow-up, and the recovery duration. All the metrics mentioned above were compared between genders with appropriate statistical methods. RESULTS: A total of 298 eyes from 280 patients (male: 51; female: 229) were enrolled. Compared with men, women demonstrated a significantly higher ratio of stage3/stage4 (P = 0.045), larger horizontal MLD (P = 0.009), but similar surgical outcomes except for a relatively longer recovery duration (P = 0.024). For stage 3 IMHs, women exhibited significantly younger age of onset (P = 0.023), larger MLD (P = 0.003), and smaller height of the hole (P = 0.029). However, for stage 4 IMHs, all the pre- and post-operative metrics showed no differences between genders. CONCLUSIONS: Female IMHs seem to demonstrate an earlier age of onset and larger size of hole, especially in IMHs of stage 3. However, these differences, which may owe to normal gender-related variations, have limited influence on the surgical outcomes.